Effect of Major Axis Length to the Pressure on Ellips - Chairul Imron; Erna Apriliani (LPPM Institut Teknologi Sepuluh Nopember, 2016)
Fluid concept has been widely applied to solve problems of daily life, one example is the problem of fluid flow around an elliptical cylinder. We have a goal to solve the problem of fluid flow through three cylindrical ellipses using side-by-side configuration. The equation we use to solve the problem is the Navier-Stokes equations, incompressible, viscous and unsteady. We use the finite difference method with a uniform grid and SIMPLE (Semi Implicit Method for Pressure-Linked Equations) algorithms. Results of this study were used to obtain the amount of pressure that is received by an ellipse in the middle and to construct mathematical models. The profile of the fluid flow is simulated by varying the length of the major axis of the ellipse in the middle where K/5a = 1.0; 1.1; 1.2; 1.3; 1.4 and 1.5 and Reynolds Re = 3.000 and the distance between the ellipse is 3.